Glasses in the NaPO3-WO3-NaF ternary system: preparation, physical properties and structural studies - Munhoz, Joao F.V.L. [UNESP]; Santagneli, Silvia Helena [UNESP]; de Oliveira, Marcos; Rodrigues, Ana Candida Martins; Eckert, Hellmut; Nalin, Marcelo [UNESP] (Elsevier, 2019)
Oxyfluoride glasses with composition x WO3 - 30 NaPO3 - (70-x) NaF, with 30 ≤ x ≤ 70 were prepared by melt-quenching and characterized with respect to their bulk physical properties and ionic conductivities. As the NaF content increases, the glass transition temperature, Tg, decreases systematically. Impedance measurements reveal no clear effect of NaF content upon room temperature electrical conductivities and activation energies. There is, however, a significant decrease of the Arrhenius pre-exponential factor with increasing WO3 content, suggesting that the electrical conductivities measured in this glass series are increasingly influenced by an electronic contribution. This contribution may be related to a W5+ → W6+ electron hopping process detected in the optical absorption spectra. Detailed spectroscopic investigations by Raman scattering and multinuclear one- and two-dimensional solid-state NMR experiments indicate that NaF acts like a network modifier resulting in the formation of W-F bonds via breakage of W-O-W and W-O-P linkages, with the former process being the preferred one. The concomitant decrease in network connectivity caused by these processes accounts for the experimentally observed decrease in glass transition temperatures with increasing NaF contents.
Keywords: Glass structure; Ionic conductivity; Mixed conductivity; Phosphate glasses; Tungsten glasses